The spectrum of biopsy proven glomerular disease in a tertiary hospital - Ayesha Aziz; Abdul Wajid (Journal of the Pakistan Medical Association, 2026)
Objective: To analyse the spectrum of biopsy-proven glomerulonephritis and associated demographic and clinical characteristics in patients undergoing ultrasound-guided renal biopsy. Method: The prospective, cross-sectional, descriptive study was conducted at the Department of Nephrology, Ayub Teaching Hospital, Abbottabad, Pakistan, from April 5, 2023, to December 30, 2024, and comprised adult patients with biopsy-proven glomerulonephritis. Clinical, demographic and laboratory data was recorded. Biopsies were performed under ultrasound guidance, and analysed via light microscopy and immunofluorescence. Estimated glomerular filtration rate was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation. Data was analysed using SPSS 23. Results: Of the 180 patients with mean age 36.79±16 years, 98(54.44%) were males and 82(45.56%) were females. There were 115(63.9%) cases of primary glomerulopathy, followed by secondary glomerulopathy 53(29.4%), vascular diseases 7(3.9%) and tubulointerstitial disease 5(2.8%). The distribution of glomerulonephritis subtypes differed significantly by age group (p<0.001). Oedema 135(74.9%) and acute kidney injury 78(43.3%) were the most common presentations, with nephrotic syndrome 129(71.7%) as the leading biopsy indication. Histopathology showed crescents 21(11.7%), post-infectious glomerulonephritis 22(12.2%), mild interstitial fibrosis and tubular atrophy 56(31.1%), and moderate-to-severe interstitial fibrosis and tubular atrophy 22(12.2%). Hypertension 81(42.5%) and diabetes 17(9.2%) were the frequent comorbidities. Conclusion: Primary glomerulopathies were predominant, while oedema and nephrotic syndrome were common findings. Key Words: Glomerulonephritis, Renal biopsy, Proteinuria, Histopathology.